Glycemic Control Modifies Difference in Mortality Risk Between Hemodialysis and Peritoneal Dialysis in Incident Dialysis Patients With Diabetes: Results From a Nationwide Prospective Cohort in Korea. Issue 11 (March 2016) - Lee, Mi Jung; Kwon, Young Eun; Park, Kyoung Sook; Kee, Youn Kyung; Yoon, Chang-Yun; Han, In Mee; Han, Seung Gyu; Oh, Hyung Jung; Park, Jung Tak; Han, Seung Hyeok; Yoo, Tae-Hyun; Kim, Yong-Lim; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although numerous studies have tried to elucidate the best dialysis modality in end-stage renal disease patients with diabetes, results were inconsistent and varied with the baseline characteristics of patients. Furthermore, none of the previous studies on diabetic dialysis patients accounted for the impact of glycemic control. We explored whether glycemic control had modifying effect on mortality between hemodialysis (HD) and peritoneal dialysis (PD) in incident dialysis patients with diabetes. A total of 902 diabetic patients who started dialysis between August 2008 and December 2013 were included from a nationwide prospective cohort in Korea. Based on the interaction analysis between hemoglobin A1c (HbA1c ) and dialysis modalities for patient survival (P for interaction = 0.004), subjects were stratified into good and poor glycemic control groups (HbA1c < or ≥8.0%). Differences in survival rates according to dialysis modalities were ascertained in each glycemic control group after propensity score matching. During a median follow-up duration of 28 months, the relative risk of death was significantly lower in PD compared with HD in the whole cohort and unmatched patients (whole cohort, hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.47–0.90, P  = 0.01; patients with available HbA1c [n = 773], HR = 0.64, 95% CI = 0.46–0.91, P  = 0.01). In the good glycemic control group, there was a significant survival advantage of PD (HbA1c <8.0%, HR = 0.59, 95% CI = 0.37–0.94, P  = 0.03). However, there was no significant difference in survival rates between PD and HD in the poor glycemic control group (HbA1c ≥8.0%, HR = 1.21, 95% CI = 0.46–2.76, P  = 0.80). This study demonstrated that the degree of glycemic control modified the mortality risk between dialysis modalities, suggesting that glycemic control might partly contribute to better survival of PD in incident dialysis patients with diabetes.